Tunneled antibiotic-impregnated vs. bolt-connected, non-coated external ventricular drainage: a comparison of complications - Ortega-Angulo, Celia; Royuela, Ana; Kalantari, Teresa; Rodríguez-Boto, Gregorio; Gutierrez-Gonzalez, Raquel (Frontiers in Neurology, 2023)
Background: External ventricular drainage (EVD) is a common emergency neurosurgical procedure, but it is not free of adverse events. The aim of this study is to compare the complication rate of two frequently used EVD types: tunneled antibiotic-impregnated catheters (BactisealÓ) and bolt-connected non-coated devices (CaminoÓ).Methods: All EVDs placed between March 1 st , 2015 and December 31 st , 2017 were registered.Procedures performed with any catheter different from BactisealÓ or CaminoÓ EVD, with incomplete follow-up and those EVDs placed due to an infectious disease were excluded.Demographic and clinical variables were collected, as well as overall complication rate (infection, hemorrhage, obstruction, malposition of the catheter, involuntary pull-out of the device) and need of replacement of the EVD.Results: A total of 77 EVDs were finally considered for analysis (40 Bactiseal®, 37 Camino®).There was a statistically significant difference in diagnosis and also in the location of the procedure, as more bolt-connected EVD were place outside the operating room (97.3% vs 23.5%, p<0.001) due to emergent pathologies like vascular diseases and spontaneous hemorrhages. In the univariate analysis, a statistically significant higher rate of catheter involuntary pull-out (29.7% vs 7.5%, p=0.012) and need of EVD replacement (32.4% vs 12.5%, p=0.035) was found in the Camino cohort. However, those differences could not be confirmed with multivariable analysis, which showed no association between the type of catheter and any of the studied complications.Ventriculostomy duration was identified as a risk factor for infection (OR 1.09, CI 95% 1.02-1.18).No significant differences were observed regarding infection, hemorrhage, obstruction, malposition, involuntary catheter pull-out, and need for EVD replacement when comparing non-impregnated bolt-connected EVDs (Camino®) with tunneled antibioticimpregnated catheters (Bactiseal®). Duration of EVD was associated with an increased risk of infection.